A Case Report and Literature Review of ANCA-Associated Vasculitis and Lupus Nephritis Overlap: Lessons in Management - Gabriel Dardik; Anna Krieger; Maya K. Rao; Michael B. Stokes; Benjamin Wooden; Andrew S. Bomback (Glomerular Diseases)
Introduction: ANCA-associated vasculitis (AAV) and lupus nephritis (LN) are distinct disease processes that both cause a nephritic picture with acute kidney injury but have different pathophysiologies and thus different treatment strategies. They also have different characteristic phenotypes on kidney biopsy. Rarely, the two processes can coincide in one patient, known as AAV-LN overlap syndrome. Case Presentation: We present the case of a 78-year-old woman who presented with a rapidly progressive kidney injury and nephritic syndrome. Initial workup suggested AAV, but further serologies and ultimately a kidney biopsy demonstrated an overlap of both AAV and LN. Management was changed after discovery of this rare syndrome. Conclusion: A low threshold for ordering serologies and early kidney biopsy are warranted in both AAV and LN as AAV-LN overlap has a unique management strategy that may respond to tailored treatment.